Trends in the global burden of vision loss among the older adults from 1990 to 2019 - Yin, Jiayang; Jiang, Bing; Zhao, Tantai; Guo, Xiaojian; Tan, Yao; Wang, Yanbing (Frontiers in Public Health, 2024)
Purpose: To quantify the global impact of vision impairment in individuals aged 65 years and older between 1990 and 2019, segmented by disease, age, and sociodemographic index (SDI).Methods: Using the Global Burden of Diseases 2019 (GBD 2019) dataset, a retrospective demographic evaluation was undertaken to ascertain the magnitude of vision loss over this period. Metrics evaluated included case numbers, prevalence rates per 100,000 individuals, and shifts in prevalence rates via average annual percentage changes (AAPCs) and years lived with disability (YLDs).